A design requirement matrix using Play Station Portable (PSP) based learning for preschool children / Nurhafizah Ahmad Zabidi - Ahmad Zabidi, Nurhafizah (2009)
English language is important for educational, cultural, personality, economic and political reasons. Learning about Play Station Portable (PSP) features, PSP can be used as a tool to help improve in learning English. However, learning English need to be taught in the suitable ways. This research aims to understand how PSP can be used to help preschool children learn English .This research employed several data collection techniques such as reviewing relevant literature review, interview and observation.